Response characteristics of mining-induced overburden strata under different degrees of regional fracturing on the roof - Jianhong WU; Junfeng PAN; Meihua FENG; Chuang LU; Jiaming GAO; Yaodong YAN; Hongyuan MA (Meitan xuebao)
To obtain the activity patterns and response characteristics of the overburden strata under different fracturing degrees of the roof, and thereby provide a reference for preventing and controlling roof-dominated rock burst through regional fracturing. Firstly, based on the microseismic monitoring results during the fracturing construction period in the ground area, the planar expansion pattern of the microseismic fracture network was characterized, and the area was divided according to the coverage of the microseismic fracture network on the working face. Then, based on theoretical analysis, the mechanism of regional fracturing leading to the release of accumulated stress and energy, the control of load sources by overlying rock structure regulation, and the self-buffering and energy absorption of the fracturing layer was revealed. Afterwards, the migration characteristics of microseismic events in different regions, the frequency characteristics of daily total energy, the distribution characteristics of energy frequency nuclear density, and the range of influence of mining on the strike direction of the working face were analyzed. Finally, the macroscopic characteristics of mining pressure manifestation and the variation characteristics of support working resistance in different regions were compared. The research results indicate that: ① the synergistic effect of regional fracturing leading to the release of accumulated stress and energy, the control of load sources by overlying rock structure, and the self-buffering and energy absorption of the fracturing layer is closely related to the degree of regional fracturing. The three recovery areas of fracturing filling zone, fracturing non-filling zone, and non-fracturing zone exhibit the microseismic response characteristics of “high frequency, low energy”, “high frequency, high energy”, and “high frequency, high energy”, respectively. The nuclear density distribution of microseismic energy frequency is consistent with it. After regional fracturing, the microseismic activity and clustering effect decrease, and the distribution of microseismic events shows a trend of migration and aggregation from the front of the work face to the back of the work face. ② The impact range of overlying rock mining is inversely proportional to the degree of regional fracturing. Regional fracturing can reduce the length of the cantilever, cut off the load transmission path, and thus reduce the impact range of advanced and inclined mining. Compared with the non-fractured zone, the impact range of advanced mining is reduced by 20.6% and 14.7%, respectively, while the impact range of inclined mining is reduced by 21.5% and 10.0%. ③ Regional fracturing can effectively alleviate the intensity of mining pressure manifestation. Regional fracturing weakens the overall integrity and strength of thick and hard rock layers, reducing the number of fractured blocks in the overlying strata and enabling them to collapse in an orderly and timely manner. Compared with the unfractured zone, the cyclic pressure pattern is unclear, and the pressure intensity is low. The continuous pressure time is shortened, the interval between pressure periods is increased, and the number of pressure cycles is reduced. ④ Based on the characteristics of overburden mining response in different extraction areas, when conducting regional fracturing construction in horizontal wells targeting thick and hard roofs, it is necessary to ensure that the regional fracturing network effectively covers the working face and the coal pillar areas on both sides of the roadway, and to avoid forming unfractured areas on the working face.